Veljekset - Maupassant, Guy de, 1850-1893 (Salt Lake City, UT : Project Gutenberg, 2014)
"Veljekset" by Guy de Maupassant is a novel written in the late 19th century. The story revolves around the lives of two brothers, Peter and John Roland, who navigate their complicated relationships within the context of family dynamics and expectations, particularly after the unexpected inheritance of a substantial fortune from a family friend. Themes of rivalry, jealousy, and the complexities of familial love are likely to be central to the narrative. At the start of the novel, we are introduced to the Roland family as they embark on a fishing trip. The family consists of the elderly Roland and his wife, joined by their two sons, Peter, a physician, and John, a younger, more impulsive character. The outing is quickly interrupted by the family$1 (Bs concerns over an impending visit from their lawyer, hinting at potential changes in their circumstances. As the plot unfolds, undercurrents of rivalry emerge, especially between the brothers as John inherits a significant fortune from a deceased friend of their father's, leading to tension and introspection about their relationships and societal positions. (This is an automatically generated summary.)s
Release date is 2014-02-17
Produced by Tapio Riikonen
Keywords: Inheritance and succession -- Fiction; France -- Social life and customs -- Fiction; Brothers -- Fiction; Normandy (France) -- Fiction; Sibling rivalry -- Fiction